Method for preparing hydrocarbon products from methyl alcohol through two-step process - BAO LIKE; DONG YUANCHUAN; DONG BAIQUAN (2016)
The invention provides a method for preparing hydrocarbon products from methyl alcohol through a two-step process. The method comprises the following steps: (1) adding preheated methyl alcohol into an etherification reactor filled with etherification catalysts for reacting to obtain a mixture containing dimethyl ether; (2) adding the mixture containing the dimethyl ether prepared by the step (1) into a light hydrocarbon reactor filled with light hydrocarbon catalysts for reacting to generate a hydrocarbon mixture; (3) cooling the hydrocarbon mixture prepared in the step (2), and separating a liquid phase part and a gas phase part; and (4) adding the gas phase part into a circulation compressor, taking at least one part of the compressed gas phase part as a circulation material, mixing the circulation material with methyl alcohol as the raw material, returning to the reactor; and subsequently separating the liquid phase part. 本发明提供由甲醇两步法制备烃类产品的方法，包括下列步骤：1)将预热的甲醇进料到装载有醚化催化剂的醚化反应器内进行反应以得到含有二甲醚的混合物；2)步骤1)所得的含有二甲醚